Long-term Prognosis of Tuberculosis Infection and Disease in Swedish Children. Issue 10 (October 2019) - Bennet, Rutger; Jonsson, Jerker; Nejat, Sahar; Olsson-Åkefeldt, Selma; Eriksson, Margareta
Abstract : Background: Reports of the outcome of treatment of tuberculosis (TB) disease and infection (TBI) in children are scarce. Since 2010, we routinely use interferon-gamma release assays in addition to clinical history for the exclusion of TBI, although the safety of this approach has been questioned. We present the frequency of recurrent TB or progression to TB after treatment for TB disease or TB infection, respectively, and progression to disease in children considered TB uninfected at our pediatric TB clinic. Methods: We included 4707 patients from 1990 to 2017. At the initial assessment, 96 (2.0%) had previously received TB treatment, 253 (5.4%) had TB disease, 1625 (35%) had TBI and 2733 (58%) children were considered uninfected. Patients were passively followed at our clinic, at the adult TB clinics in Stockholm and at the Swedish national TB registry. Results: During a median follow-up time of 8.4 years, we found 36 cases of TB disease, with true relapses in 3/243 (1.2%) successfully treated TB patients. Preventive treatment of TBI reduced the risk of progression to TB by 85%, from 4.3% (15/349) to 0.6% (8/1262). In children considered uninfected, the risk of later developing TB was 0.07% (2/2733). Conclusions: The effectiveness of TB management was acceptable. Our routine procedures for the exclusion of TBI appear safe.